2015
DOI: 10.1016/j.pmrj.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ABO Blood Type on Rotator Cuff Tears

Abstract: Patients with rotator cuff tears were more likely to have blood type O. The odds ratios of factors for rotator cuff tears were high in the following order: major trauma history, blood type O, minor trauma history, and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…After reading the title and abstract, we were left with 56 articles. After re-reading the full text, we excluded 30 articles that did not meet the inclusion criteria, and leaving 26 articles [ 1 , 4 , 5 , 9 , 10 , 16 , 17 , 20 , 24 , 27 , 28 , 29 , 31 , 34 , 37 , 40 , 41 , 43 , 44 , 48 , 49 , 56 , 58 , 61 , 62 , 64 ] in our study (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After reading the title and abstract, we were left with 56 articles. After re-reading the full text, we excluded 30 articles that did not meet the inclusion criteria, and leaving 26 articles [ 1 , 4 , 5 , 9 , 10 , 16 , 17 , 20 , 24 , 27 , 28 , 29 , 31 , 34 , 37 , 40 , 41 , 43 , 44 , 48 , 49 , 56 , 58 , 61 , 62 , 64 ] in our study (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…3). 19,21–24 In our meta-analysis based on these studies, current smokers were approximately 2 times more likely to have rotator cuff disease compared with nonsmokers (OR = 1.94, 95% CI = 1.52–2.48; Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…Of the 212 articles eligible for full-text review, seven studies reported on the relationship between age and rotator cuff disease, [14][15][16][17][18][19][20] and 10 studies reported on the relationship between smoking and rotator cuff disease (Table 1; Appendix 1, Supplemental Digital Content 2, http://links.lww.com/PHM/ B329). 12,14,[19][20][21][22][23][24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…RCT is common in the distal vascular supply of the supraspinatus tendon or infraspinatus tendon and is known as the “risk area” for rotator cuff injury. Therefore, the affected shoulder has been injured, resulting in chronic loss of blood supply and rotator cuff tears ( 33 , 35 ).…”
Section: Discussionmentioning
confidence: 99%